Weaponized Lies: How to Think Critically in the Post-Truth Era - Daniel J. Levitin (Dutton, 2017)
We’re surrounded by fringe theories, fake news, and pseudo-facts. These lies are getting repeated. New York Times bestselling author Daniel Levitin shows how to disarm these socially devastating inventions and get the American mind back on track. Here are the fundamental lessons in critical thinking that we need to know and share now.